2006
DOI: 10.1021/ol061791y
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Structures of Novel Heteroarene-Fused Coplanar π-Conjugated Chromophores

Abstract: We have synthesized a series of novel coplanar chromophores in which heteroarenes, namely, thiophene, benzothiophene, and carbazole, were fused to neighboring phenylene ring(s) through intramolecular annulation via sp(3)-hybridized carbon atoms bearing two p-tolyl groups as peripheral substituents. The molecular configurations of the pi-conjugated backbones were determined by X-ray crystallographic analysis; the heteroarene-fused molecular frameworks of these novel molecules exhibit nearly coplanar conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 29 publications
4
67
0
Order By: Relevance
“…11 Recently, Wong et al have designed and synthesized a novel coplanar chromophore that feature phenylene ring(s) fused to thiophene, namely, phenylene-thiophene-phenylene (TPT) derivatives. 12 The molecular configurations of the π-conjugated backbones are confirmed through X-ray crystallography, and the heteroarene-fused molecular frameworks of the TPT unit exhibit nearly coplanar conformations. In this paper, we present a series of novel coplanar semiconducting polymers, which are the first new class of copolymers utilizing a TPT derivative as the fused coplanar unit in the polymer chain.…”
Section: Introductionmentioning
confidence: 88%
“…11 Recently, Wong et al have designed and synthesized a novel coplanar chromophore that feature phenylene ring(s) fused to thiophene, namely, phenylene-thiophene-phenylene (TPT) derivatives. 12 The molecular configurations of the π-conjugated backbones are confirmed through X-ray crystallography, and the heteroarene-fused molecular frameworks of the TPT unit exhibit nearly coplanar conformations. In this paper, we present a series of novel coplanar semiconducting polymers, which are the first new class of copolymers utilizing a TPT derivative as the fused coplanar unit in the polymer chain.…”
Section: Introductionmentioning
confidence: 88%
“…These structural features may reduce the excimer formation in solid film as already observed for similar structures. [75,76] Thermal properties of DSF-IF derivatives: Thermal properties were examined using thermogravimetric (TGA) and differential scanning calorimetry (DSC) analyses. The glass transition (T g ), melting transition (T m ), crystallisation (T c ) and decomposition (T d ) temperatures are summarised in Table 1.…”
Section: Synthesis Of Dsf-if Derivativesmentioning
confidence: 99%
“…Indacenodithiophene (IDT) has been paid much attention in the design of new conjugated copolymers for the application in the solar cells [110]. The coplanarity of the IDT unit could enhance the interchain interaction of the polymers and be expected to have higher hole mobility [111]. A polymer P53 composed of BT jointing with alkyl-substituted indacenodithiophene was presented by Zhang et al P53 revealed a better solubility in many organic solvents.…”
Section: Polymers Containing 213-benzothiadiazolementioning
confidence: 99%